Highly efficient catalytic oxidation of 5-hydroxymethylfurfural to 2, 5-furandicarboxylic acid using bimetallic Pt–Cu alloy nanoparticles as catalysts. Issue 8 (4th January 2022) - Cheng, Xiaomeng; Li, Shaopeng; Liu, Shulin; Xin, Yu; Yang, Junjuan; Chen, Bingfeng; Liu, Huizhen
Abstract : Bimetallic Pt–Cu alloy nanoparticles were used as highly active and selective catalysts for the oxidation of 5-hydroxymethylfurfural (HMF) to 2, 5-furandicarboxylic acid (FDCA) under base-free conditions. Abstract : Bimetallic platinum– copper alloy nanoparticles are highly active catalysts for the oxidation of 5-hydroxymethylfurfural (HMF) to 2, 5-furandicarboxylic acid (FDCA) under base-free conditions, with a high turnover frequency of up to 135 h −1 in aqueous solution. The Pt–Cu1.5 /AC alloyed catalyst promoted the rate-determining step in the tandem oxidation compared with the monometallic Pt/AC catalyst, thus improving the catalytic performance.